Modularity in cooperative product development: the case of the MCC 'smart' car. (11th July 2008) - Stephan, Michael; Pfaffmann, Eric; Sanchez, Ron
This paper investigates the relationships between the product development processes, modular product architectures and a modular interfirm organisation. We use the case of Micro Compact Car (MCC), the company that developed and produced the 'smart' city car and is now a division of Daimler. We examine the ways in which the company applied a revolutionary approach to outsourcing, early supplier involvement and quasi-integration and a 'modular' organisation. The paper also suggests some deficiencies in MCC's initial approach and proposes a framework for assessing architectural capabilities in product development, intended to improve the organisation of collaborative modular development projects.